The Effectiveness of SAVI Approach-based Teaching Materials Oriented to Mathematical Connection Ability - Muhammad Daut Siagian; Suwanto Suwanto; Rini Sulastri (Didaktik Matematika, 2020)
This study aims to analyze the effectiveness of SAVI approach-based teaching materials developed for mathematical connection ability. This study was research and development. The subjects were 36 Grade 8 students and a mathematics teacher and the objects were the SAVI approach-based teaching materials oriented to the mathematical connection ability. The effectiveness of the teaching materials measured by four aspects: (1) the observation of the teacher's ability to manage the learning should at least be in the "good" category, (2) six of the eight aspects of students activities are within the ideal time interval, (3) the students' mastery learning are fulfilled both individually and classically, and (4) the student and teacher questionnaire responses show positive responses. The results revealed that the effectiveness criteria were fulfilled. The observation of the teacher's ability to manage the learning was in the very good category (4.22). The student activities in learning was within the threshold for achieving the ideal time. Also, The students mathematical connection ability satisfied the mastery learning individually and classically (84.11%). The teacher and student questionnaire responses showed positive responses. Thus, the SAVI approach-based teaching materials oriented to mathematical connection ability are feasible as a learning resource for students in learning mathematics.